2001
DOI: 10.1016/s0032-3861(00)00485-7
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric relaxation spectroscopy of reactively blended amorphous poly(ethylene terephthalate)–poly(ethylene naphthalate) films

Abstract: Reactively blended poly(ethylene terephthalate)-poly(ethylene naphthalate) films of different compositions and degrees of ester exchange reaction have been investigated by dielectric relaxation spectroscopy. The a-relaxation peaks associated with the glass transition have been fitted by the semi-empirical Havriliak-Negami relaxation function to frequency scans. The parameter relating to relaxation broadness, b, and the relaxation strength, D1 , were quantified and were found to be a parameter sensitive to proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 13 publications
(20 reference statements)
5
27
0
1
Order By: Relevance
“…The dielectric loss spectra can be further studied by applying the well-known Havriliak-Negami (HN) function [30] as follows,…”
Section: Resultsmentioning
confidence: 99%
“…The dielectric loss spectra can be further studied by applying the well-known Havriliak-Negami (HN) function [30] as follows,…”
Section: Resultsmentioning
confidence: 99%
“…The slope of the line for the best fit through the ln(f m ) versus 1/T can be used to calculate the activation energy. 24 The SAN/MMA-MA systems present higher activation energy than neat SAN which is related to a lower mobility of polymeric chain in the SAN/MMA-MA system due to the miscibility between SAN and MMA-MA.…”
Section: Study Of the Miscibility Of San/mma-ma Blendsmentioning
confidence: 98%
“…It is noted that while T g represents the relationship between the mobility of polymer chains and temperature, peak temperature is decreased by about 6 2 78C when frequency goes from 1 to 50 Hz. It has been suggested that it is possible to interrelate the temperature at which a relaxation process is observed with the frequency of excitation (ƒ) by the Arrhenius equation (especially over a limited frequency range), which predicts change in relaxation time as the glass transition is approached from above T g due to the decrease of free volume [29,30]. According to the classic Arrhenius equation, molecular relaxation time(s) may be expressed as follows:…”
Section: Calculation Of the Activation Energymentioning
confidence: 99%